Pengaruh Kepercayaan dan Pengetahuan Zakat Terhadap Minat Membayar Zakat, infaq Sedekah melalui Lazisnu Kota Kraksaan (studi pada masyarakat Kabupaten Probolinggo) - Sari, Lutfiah Novita; suprayitno, eko; ekowati, vivin maharani; AR, Sri Wahyuni Safitri (ITB AAS INDONESIA Surakarta, 2024)
ZIS is a financial instrument that is quite potential in Indonesia and Probolinggo Regency in particular, but the collection of ZIS at Lazisnu Kota Kraksaan from year to year has not reached the target. Therefore, it is important to know the factors that influence people's interest in paying ZIS. This study aims to determine whether there is an influence between trust on the interest in paying ZIS through Lazisnu Kota Kraksaan, knowledge of zakat on the interest in paying ZIS through Lazisnu Kota Kraksaan, and whether trust and knowledge of zakat together influence the interest in paying ZIS through Lazisnu Kota Kraksaan. This study uses a quantitative method with secondary data and primary data. Secondary data in this study were obtained from books, journals and other related scientific studies. While the primary data in this study were obtained from questionnaires distributed online via WhatsApp social media, in addition, researchers also distributed questionnaires directly to people who were less active in social media. This study obtained the results of a) trust has a significant effect on the interest in paying ZIS through Lazisnu Kota Kraksaan, as seen from the calculated t value X1> T table or 4.882> 1.894 and the Sig. value 0.001 T table or 4.096> 1.894 and the Sig. value 0.001 F table or 32.413> 3.090 with a Sig. value 0.001